Adherence and Persistence to Antiplatelet Therapy in Lower Extremity Peripheral Arterial Disease: A Danish Population Based Cohort Study - Thaarup, Maja; Jacobsen, Sara; Nielsen, Peter Brønnum; Nicolajsen, Chalotte Winther; Eldrup, Nikolaj; Petersen, Christian Nikolaj; Behrendt, Christian-Alexander; Dahl, Marie; Højen, Anette Arbjerg; Søgaard, Mette (European journal of vascular and endovascular surgery, 2024)
Adherence to antiplatelet therapy is recommended but unexplored in patients with symptomatic lower extremity peripheral arterial disease (PAD). Therefore, this study aimed to determine adherence and persistence to antiplatelet therapy in patients with PAD, defined as intermittent claudication and chronic limb threatening ischaemia. Population based nationwide cohort study. This study included all Danish citizens aged ≥ 40 years with a first inpatient or outpatient diagnosis of symptomatic PAD between 2010 – 2017, and who had at least one prescription claim for aspirin and/or clopidogrel within 90 days after diagnosis. Adherence was determined by the proportion of days covered (PDC) during the first year after diagnosis. Persistence was defined as no treatment gap ≥ 30 days between prescription renewals over three year follow up. A total of 39 687 patients were eligible for inclusion, of whom 23 279 (58.7%) claimed a prescription for aspirin and/or clopidogrel within 90 days of diagnosis. Among these, 12 898 (55.4%) were prevalent users, while the remainder comprised new users who initiated the therapy after the index PAD diagnosis. The mean PDC was 74.5% (SD 35.0%) for prevalent users and 60.5% (SD 30.5%) for new users. Adherence increased with age and number of concomitant drugs. The overall one year cumulative incidence treatment discontinuation was 13.0% (95% CI 12.5 – 13.4%) overall, 17.2% (CI 16.6 – 17.9%) for prevalent users, and 7.9% (CI 7.4 – 8.4%) for new users. At three year follow up, the cumulative incidence of discontinuation was 31.5% (CI 30.9 – 32.2%) overall, 44.6% (CI 43.7 – 45.4%) for prevalent users, and 14.6% (CI 13.9 – 15.3) for new users. Less than 60% of patients with newly diagnosed symptomatic PAD claimed a prescription for antiplatelet therapy within 90 days of diagnosis, and both adherence and persistence were moderate during the first year after diagnosis. These findings underscore the importance of efforts to improve the initiation and continuation of antiplatelet therapy in patients with PAD.